Co‐precipitation of DEAE‐dextran coated SPIONs: how synthesis conditions affect particle properties, stem cell labelling and MR contrast†. (30th June 2016) - Barrow, Michael; Taylor, Arthur; García Carrión, Jaime; Mandal, Pranab; Park, B. Kevin; Poptani, Harish; Murray, Patricia; Rosseinsky, Matthew J.; Adams, Dave J.
Abstract : Superparamagnetic iron oxide nanoparticles (SPIONs) are widely used as contrast agents for stem cell tracking using magnetic resonance imaging (MRI). The total mass of iron oxide that can be internalised into cells without altering their viability or phenotype is an important criterion for the generation of contrast, with SPIONs designed for efficient labelling of stem cells allowing for an increased sensitivity of detection. Although changes in the ratio of polymer and iron salts in co‐precipitation reactions are known to affect the physicochemical properties of SPIONs, particularly core size, the effects of these synthesis conditions on stem cell labelling and magnetic resonance (MR) contrast have not been established. Here, we synthesised a series of cationic SPIONs with very similar hydrodynamic diameters and surface charges, but different polymer content. We have investigated how the amount of polymer in the co‐precipitation reaction affects core size and modulates not only the magnetic properties of the SPIONs but also their uptake into stem cells. SPIONs with the largest core size and lowest polymer content presented the highest magnetisation and relaxivity. These particles also had the greatest uptake efficiency without any deleterious effect on either the viability or function of the stem cells. However, for all particles internalised in cells, the T2 and T2 * relaxivity was independent of the SPION's core size. Our results indicate that the relative mass of iron taken up by cells is the major determinant of MR contrast generation and suggest that the extent of SPION uptake can be regulated by the amount of polymer used in co‐precipitation reactions. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We have investigated how the amount of polymer in the co‐precipitation reaction affects core size and modulates not only the magnetic properties of the SPIONs but also their uptake into stem cells. Our results indicate that the relative mass of iron taken up by cells is the major determinant of MR contrast generation and this can be tuned by changing the amount by changing the amount of polymer used in the synthesis.